GPT AI Chat: Revolutionizing Education for Civil Engineering Student Performance: Revolusi Pendidikan: Dampak Chat GPT AI pada Efisiensi Kurikulum dan Prestasi Mahasiswa Teknik Sipil - Muhammad Alvan Rizki; Mahardika Darmawan Kusuma Wardana; Hendri Hermawan (Academia Open, 2023)
This literature review investigates the influence of Chat GPT AI on the effectiveness of the civil engineering curriculum and student performance. The study explores the use of Chat GPT AI in education and emphasizes the significance of rubric assessment in evaluating student achievements. The findings reveal that incorporating Chat GPT AI can significantly enhance the learning process by providing prompt and accurate responses to students' queries. However, the study emphasizes the continued importance of human interaction in the assessment process, as rubric assessment remains crucial for evaluating student performance and fostering motivation for better outcomes. The implications underscore the need to align the curriculum with industry standards and leverage technology to enrich the learning experience. These findings hold potential for educators and policymakers seeking to enhance educational quality and produce highly qualified civil engineering graduates. Highlights: Chat GPT AI: Improving Efficiency - The study explores the impact of Chat GPT AI in civil engineering education, highlighting its potential to enhance the efficiency of the learning process by providing quick and accurate answers to students' questions. Importance of Rubric Assessment - The research emphasizes the crucial role of rubric assessment in measuring student performance and motivating them to achieve better results, highlighting its significance alongside the integration of technology. Adapting Curriculum and Utilizing Technology - The study highlights the importance of adapting the curriculum to meet industry needs and standards, while also leveraging technology, such as Chat GPT AI, to enhance the learning experience and improve the quality of civil engineering education. Keywords: Chat GPT AI, civil engineering education, curriculum efficiency, student performance, rubric assessment.